Exercising self-control increases approach motivation.[article]. - Schmeichel, Brandon J.
The present research tested the hypothesis that exercising self-control causes increase in approach motivation. Study 1 found that exercising (vs. not exercising) self-control increases self-reported approach motivation. Study 2a identified a behavior-betting on low-stakes gambles -that is correlated with approach motivation but is relatively uncorrelated with self-control, and study 2b observed that exercising self-control temporarily increases this behavior. Last, Study 3 found that exercising self-control facilitates the perception of a reward-relevant symbol(i. e., a dollar sign) but not a reward-irrelevant symbol (i, e., a percent sign). Altogether, these results support the hypothesis that exercising self-control temporarily increases approach motivation. Failure of self-control that follow from prior efforts at self-control (i. e., ego depletion) may be explain in part by increased approach motivation. -- (from the athor)
Keywords: Approach motivation; Ego depletion; Reinforcement sesitivity theory; Self-control.; Self-regulation.